International Class Program Student Management at PTKIN (A Study at UIN Salatiga and UINSI Samarinda) - Siti Julaiha; Fathul Janah (Southeast Asian Journal of Islamic Education, 2023)
Higher education institutions are responsible for producing graduates who are competitive at local, national, and international levels. One of the breakthroughs made by higher education institutions is an international class program as a distinction and excellence to answer problems in the era of the Industrial Revolution 4.0. The purpose of this study was to find out the management of international class students at UIN Salatiga and UINSI Samarinda. This type of research is qualitative research using a multi-case approach with data collection techniques in the form of observation, interviews, and documentation. The data analysis technique was interactive data analysis. The findings from this research are that the management of international class students at UIN Salatiga and UINSI Samarinda in terms of recruitment is carried out strictly (Arabic and English tests, TPA, interviews). The difference is that at UIN Salatiga all students from various study programs can take part in the selection or recruitment of international classes, while at UINSI Samarinda the selection for international classes is only for the Islamic Religious Education Study Program (PAI). International class learning at UIN Salatiga and UINSI Samarinda use the (regular) curriculum for each study program and then add additional curricula covering foreign languages ​​both Arabic and English, Qur’an memorization, art, or local wisdom. The findings also show some challenges in the implementation of student management such as in the aspect of the curriculum, lecturer’s ability in foreign language use, and the absence of alumni association. Best practice from the results of this research is expected to be applied and becomes a reference for other higher education institutions to have and run international class programs.